1982
DOI: 10.1016/0304-3959(82)90135-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of propranolol in post-traumatic neuralgia

Abstract: In view of several case reports of relief of various neuralgias by propranolo, a double-blind cross-over trial using this drug was conducted in 10 patients with severe persistent pain and paraesthesiae following upper limb peripheral nerve injuries. The patients received up to 240 mg of propranolol per day. Only one patient reported pain relief, but this patient withdrew from the trial. An open trial of propranolol was conducted in 6 other patients with a variety of peripheral nerve lesions. Of these, neuroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 20 publications
1
12
0
4
Order By: Relevance
“…Topical application of the a2 adrenergic receptor agonist, clonidine, relieves hyperalgesia in SMP patients . Blockade of adrenergic receptors with phentolamine Treede et al, 1991), phenoxybenzamine or prasozin have also shown efficacy in aUeviating SMP (Abram and Lightfoot, 1981;Ghostine et al, 1984), while the ~-adrenergic receptor antagonist, propanolol, does not show as much efficacy in SMP (Scadding et al, 1982;Raja et al, 1991). Peripheral application of NE can cause exacerbation of the hyperalgesia from complete Freund's adjuvantinduced neuritis (Baik et al, 2003), while intradermal injection of NE or a-adrenergic agonists can rekindle pain and hyperalgesia in patients and animaIs which had been relieved by sympathectomy or sympathetic block (Wallin et al, 1976;Xie et a1., 1995;Moon et al, 1999).Results from Ali et al (1999), suggest it is the uninjured C-fibres that develop a-adrenergic sensitivity and hyperactivity after nerve injury.…”
Section: Role Of Adrenergic Sensitivity In Neuropathic Pain After CCImentioning
confidence: 99%
“…Topical application of the a2 adrenergic receptor agonist, clonidine, relieves hyperalgesia in SMP patients . Blockade of adrenergic receptors with phentolamine Treede et al, 1991), phenoxybenzamine or prasozin have also shown efficacy in aUeviating SMP (Abram and Lightfoot, 1981;Ghostine et al, 1984), while the ~-adrenergic receptor antagonist, propanolol, does not show as much efficacy in SMP (Scadding et al, 1982;Raja et al, 1991). Peripheral application of NE can cause exacerbation of the hyperalgesia from complete Freund's adjuvantinduced neuritis (Baik et al, 2003), while intradermal injection of NE or a-adrenergic agonists can rekindle pain and hyperalgesia in patients and animaIs which had been relieved by sympathectomy or sympathetic block (Wallin et al, 1976;Xie et a1., 1995;Moon et al, 1999).Results from Ali et al (1999), suggest it is the uninjured C-fibres that develop a-adrenergic sensitivity and hyperactivity after nerve injury.…”
Section: Role Of Adrenergic Sensitivity In Neuropathic Pain After CCImentioning
confidence: 99%
“…50 A previous case cross-over trial found no evidence of effectiveness with propranolol in patients with neuropathic pain 51 , whereas a trial in patients with a myogenous pain disorder suggested a benefit with propranolol in our study population. 52 Thus it is conceivable that β-adrenoreceptor antagonists in general (or propranolol in particular) are more effective in nociceptive than neuropathic pain.…”
Section: Discussionmentioning
confidence: 65%
“…50 Interestingly, blockade of ␤-adrenoceptors does not relieve symptoms in RSD patients. 51 Overall, these data suggest that the ␣-, but not the ␤-adrenoceptor is involved in mediation of pain.…”
Section: Treatmentmentioning
confidence: 85%